Contribution of Penglipuran Village Festival as A Form of Development of Contemporary Tourism Products in Penglipuran Bangli Village, Bali - Kristina Putri, Komang Shintiya Nita; Karina Putri, Ida Ayu; Tiana Raditya, I Putu; Pramana Putra, Putu Guntur (Jurnal Manajemen Pelayanan Hotel, 2022)
Penglipuran Village Festival is one of the festivals located in Penglipuran Tourism Village, Bangli Regency, Bali. This festival has been running for 9 years. Through this festival a fhas been provided local community forum in order to innovate the products offered from this village, besides that through the existence of this contemporary festival it can also help to promote the Penglipuran Tourism Village. This research used a qualitative approach with data collection methods through literature studies, observations, interviews and documentation. The Penglipuran Village Festival has a space for supporting preservation of the traditions and culture that have been attached to the Penglipuran Tourism Village. In addition, Penglipuran Village Festival also provides space to communicate and build relationships with the parties involved. And the last one, Penglipuran Village Festival, provides a space for young people to express themselves through their visions and creativies. Keywords: Village Festival Festival, Contributary, Contemporary, Penglipuran Village, Bangli.